Maize Rotation Combined with Streptomyces rochei D74 to Eliminate Orobanche cumana Seed Bank in the Farmland - Jiao Xi; Zanbo Ding; Tengqi Xu; Wenxing Qu; Yanzhi Xu; Yongqing Ma; Quanhong Xue; Yongxin Liu; Yanbing Lin (Agronomy, 2022)
Orobanche cumama wallr. is the sunflower root parasitic weed with special life stage in which seed germination and parasitism take place in the soil. In practice, applying microbial agents and trapping crop rotation are utilized separately, or just one of them is selected to control O. cumana. The development of the sunflower industry is severely constrained on the farmland, where there is high density of O. cumana’s seed banks. In this study, two biological control methods were combined to solve the problem of O. cumana parasitism. The bioassay experiment showed that the high concentration fermentation filtrates of Streptomyces rochei D74 could effectively inhibit the germination and growth of the germ tube of O. cumana seeds. As the concentration was increased to 3.1 mg/mL, O. cumana was almost unable to sprout. A two-year pot experiment revealed that the use of D74 agents and sunflower–maize–sunflower rotation together promoted sunflower growth, as shown by the biomass accumulation, plant height, and denser root systems. The combined method resulted in a significant decrease in the number of O. cumana parasitism, compared to one method alone. Additionally, it affected the bacterial community composition of sunflower rhizosphere, mostly leading to an increase in Streptomyces and Brevibacterium and a decrease in Arthrobacter. This experiment, combined with multiple biological control, means significantly reducing the parasitism of O. cumana, which provides an effective foundation for practical application.